An Up-to-Date Correlation of Epidemiological and Histopathological Characteristics of Basal Cell Carcinoma of the Skin in a County Hospital in Romania - Iuliu Gabriel Cocuz; Maria Elena Cocuz; Adrian-Horațiu Sabău; Raluca Niculescu; Andreea Cătălina Tinca; Vlad Vunvulea; Corina Eugenia Budin; Mihaela Cornelia Șincu; Maria Cătălina Popelea; Ovidiu Simion Cotoi (MDPI AG, 2022)
Background and Objectives: Basal carcinoma of the skin (BCC) is part of the nonmelanoma skin cancer (NMSC) family and is the most frequently occurring type of skin cancer in humans. A combination of clinical and histopathological approaches is necessary in order to establish the best treatment regime for patients who have been diagnosed with this type of cancer. The objective of the present study was to establish the statistical value of prediction for certain sociodemographic characteristics (age category and environment of origin) and histopathological parameters of the subjects that could be related to the incidence of diagnosis with certain histopathological subtypes of BCC. Materials and Methods: In order to verify the veracity of the established research hypotheses, we conducted a retrospective study based on the histopathological reports of 216 patients who were treated at the Pathology Department of Mureș Clinical County Hospital. Results: Cystic BCC is higher in patients who are older than 71 years of age, and the superficial multicentric and keratotic subtypes are more frequently diagnosed in urban areas. Patients who have been diagnosed with the superficial multicentric BCC subtype are not usually very old in contrast to the patients who tend to be diagnosed with the cystic BCC subtype. The nodular BCC subtype is positively associated with ulceration (p = 0.004); the superficial multicentric BCC subtype is positively associated with intra- and peritumoral inflammatory infiltrate (p = 0.022, p = 0.034) and negatively associated with ulceration (r = −0.218, p = 0.001). The infiltrative BCC subtype is positively associated with ulceration (p = 0.021), and the keratotic BCC subtype is positively associated with peritumoral inflammatory infiltrate (p = 0.02). Conclusions: Depending on each patient's epidemiological and sociodemographic data, a pattern can be established regarding the appropriate clinical and treatment approaches for that patient, which can be supported based on the implications of the histopathological diagnostic. This can lead to an improvement in the patient's quality of life and increased satisfaction with the provided medical services.